Odpowiedzi

Najlepsza Odpowiedź!
2010-04-11T16:37:17+02:00
A)
1
-- x - 2 = x+2
3

-2-2=x - 1/3 x
-4 = 2/3 x \ * 3/2
-12/2 = x
-6 = x

b)
1 - 6/7 x = 4/7 \ *7
7-6x=4
7-4=6x
3=6x \ /6
0,5 = x

c)
6( 1/4 x - 2) = 18
6/4 x - 12 = 18
6/4 x = 18 +12
6/4 x = 30
1,5 x = 30
x = 20

d)
x/6 - 1/6 = 1 \ *6
x-1=6
x= 6+1
x=7



e)
-2(2x - 1)=x/3
-4x + 2 = x/3 \ *3
-12x + 6 = x
6 = x + 12x
6 = 13x
6/13 = x


;))



2010-04-11T16:47:12+02:00
1.
x-1/3x=-4
2/3x=-4
x=-6

2.
-6/7x=4/7-7/7
-6/7x=-3/7 (mnozymy przez -7/6)
x=1/2

3.
6(1/4x-2)=18
1,5x-12=18
1,5x=30
x=20

4.
x/6-1/6=1 (mnozymy przez 6)
x-1=6
x=7

5.
-2(2x-1)=x/3
-4x+2=x/3 (mnozymy przez 3)
-12x+6=x
-13x=-6
x=6/13